ISFM Consensus Guidelines on the Diagnosis and Management of Hypertension in Cats. Issue 3 (March 2017) - Taylor, Samantha S; Sparkes, Andrew H; Briscoe, Katherine; Carter, Jenny; Sala, Salva Cervantes; Jepson, Rosanne E; Reynolds, Brice S; Scansen, Brian A
Practical relevance: Feline hypertension is a common disease in older cats that is frequently diagnosed in association with other diseases such as chronic kidney disease and hyperthyroidism (so-called secondary hypertension), although some cases of apparent primary hypertension are also reported. The clinical consequences of hypertension can be severe, related to 'target organ damage' (eye, heart and vasculature, brain and kidneys), and early diagnosis followed by appropriate therapeutic management should help reduce the morbidity associated with this condition. Clinical challenges: Despite being a common disease, routine blood pressure (BP) monitoring is generally performed infrequently, probably leading to underdiagnosis of feline hypertension in clinical practice. There is a need to: (i) ensure BP is measured as accurately as possible with a reproducible technique; (ii) identify and monitor patients at risk of developing hypertension; (iii) establish appropriate criteria for therapeutic intervention; and (iv) establish appropriate therapeutic targets. Based on current data, amlodipine besylate is the treatment of choice to manage feline hypertension and is effective in the majority of cats, but the dose needed to successfully manage hypertension varies between individuals. Some cats require long-term adjuvant therapy and, occasionally, additional therapy is necessary for emergency management of hypertensive crises. Evidence base: These Guidelines from the International Society of Feline Medicine (ISFM) are based on a comprehensive review of the currently available literature, and are aimed at providing practical recommendations to address the challenges of feline hypertension for veterinarians. There are many areas where more data is required which, in the future, will serve to confirm or modify some of the recommendations in these Guidelines.